Crises and the Roman Empire Proceedings of the Seventh Workshop of the International Network Impact of Empire (Nijmegen, June 20-24, 2006) - Hekster, Olivier; de Kleijn, Gerda; Slootjes, Daniëlle (Impact of Empire, 2007)
This volume presents the proceedings of the seventh workshop of the international thematic network Impact of Empire, which concentrates on the history of the Roman Empire. It focuses on the impact that crises had on the development and functioning of the Roman Empire from the Republic to Late Imperial times. Readership: All those interested in Roman history (also at the local level in communities in the Roman Empire), the transformations of the Roman Empire in the crises of the Late Republic and Third Century, and the reality and perception of periods of crisis in the Roman Empire.